KONSEP JIHAD DALAM SHAHIH AL-BUKHARI (STUDI ANALISIS JIHAD KITAB FATH AL-BARI KARYA IBNU HAJAR AL-ASQALANI) - Suhandoko, Suhandoko (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Jihad is always associated with the term war, ignorance of the meaning of jihad leads to a deviation from the true meaning of jihad. So that people are very easily infiltrated about radicalism ideas, as a result there are anarchist actions and even suicide bombings occur in the name of their actions as part of jihad. In this study the author used the library research method, by going through various sources of primary data, namely in the form of books, the book of authentic hadith al-Bukari and the book of Syarah Fath al-Bari as well as other books, and secondary data which contains writings which is useful with the subject matter and studied comes from articles, journals and internet sites. After conducting this research, it can be seen how the concept of jihad is in accordance with the provisions of Islamic law, especially in the hadiths of Sahih al-Bukhari and also in the syarah books, especially in the book of Syarah Fath al-Bari which explains jihad, that in this study jihad is not only identified with war, but is very broad, including jihad on parents, jihad against passions and others, so that after this research we can find out how the concept of jihad is in accordance with Islamic teachings so that we are not easily exposed to radical ideas. Hopefully in the future, people's lives can be realized based on noble moral values as taught by Rasulullah SAW. And eliminate all forms of misunderstanding regarding the meaning of jihad.